Manajemen e-book di UPT Perpustakaan Universitas Negeri Semarang melalui sistem aplikasi - Setyarini - -; Pasca Kalisa; Annisa Dwi Cahyaningtyas (FPPTI Jawa Tengah, 2021)
A Vitual or Digital Library is one of the systems that has many types of services as well as information objects that support access from those information objects through a digital device. The ebook management managed by Unnes Library aims to provide ease in searching for information such as pictures, documents, as well as databases in digital formats quickly, precisely, and accurately. Collection on a digital library is not limited to electronic documents substituting print books alone, but collection is emphasized on the contents of information, the type from the documents to the results of its tracing. ebook management is essentially an ebook cataloguing program itself. The software stores countless ebook files in a database along with its metadata. eBook is the equivalent of conventional books, the difference in writing is inside digital media. The ebook is read through certain software, commonly referred to as the ebook reader. Even ebook file formats vary, some are pdfs that can be opened with acrobat reader. There are also html-shaped, openable ones with browsing/internet exploration. ebook is an electronic version of a printed book, if the book is generally composed of paper sets while ebook is digital information that can contain pictures or text. In the digital age ebooks began to be in demand because they were small in size, easily accessible anywhere, had more interesting search features, too, the words could be easily as well as quickly rediscovered when searched. It is in this context that the Unnes Library realized its commitment as a House of Sciences that wants to upgrade conventional library services to digital/virtual libraries, which is an accelerated part of innovation by utilizing the ebook Management application as as the management of Electronic Books that have been collected by the Unnes Library.